Oxygen—A Critical, but Overlooked, Nutrient - Trayhurn, Paul (Frontiers in Nutrition, 2019)
Gaseous oxygen is essential for all aerobic animals, without which mitochondrial respiration and oxidative phosphorylation cannot take place. It is not, however, regarded as a ‘nutrient’ by nutritionists and does not feature as such within the discipline of nutritional science. This is primarily a consequence of the route by which O2 enters the body, which is via the nose and lungs in terrestrial animals as opposed to the mouth and gastrointestinal tract for what are customarily considered as nutrients. It is argued that the route of entry should not be the critical factor in defining whether a substance is, or is not, a nutrient. Indeed, O2 unambiguously meets the standard dictionary definitions of a nutrient, such as ‘a substance that provides nourishment for the maintenance of life and for growth’ (Oxford English Dictionary). O2 is generally available in abundance, but deficiency occurs at high altitude and during deep sea dives, as well as in lung diseases. These impact on the provision at a whole-body level, but a low pO2 is characteristic of specific tissues includings the retina and brain, while deficiency, or overt hypoxia, is evident in certain conditions such as ischaemic disease and in tumours - and in white adipose tissue in obesity. Hypoxia results in a switch from oxidative metabolism to increased glucose utilisation through anaerobic glycolysis, and there are extensive changes in the expression of multiple genes in O2-deficient cells. These changes are driven by hypoxia-sensitive transcription factors, particularly hypoxia-inducible factor-1 (HIF-1). O2 deficiency at a whole-body level can be treated by therapy or supplementation, but O2 is also toxic through the generation of reactive oxygen species. It is concluded that O2 is a critical, but overlooked, nutrient which should be considered as part of the landscape of nutritional science.